(3QhVI GdCdHG aj JGQjN GdCWHGs - (3OGhO Hf fGUQ GdOjf GdGZHQj GdehUdj GdMUcaj GdehUdj , WHjH GdOhdJjf,J (B829 (3g` s
(3ChdgG (B:s
(3hHYO deG WHYJ GdfahS Ydi GdHMK Yf GdSGdaGJ aCQOJ JPjjd JGQjN GdCWHGA ddOhdI GdCTQajI GdZQG , hSejJg HQhVg GdCdHG ai JGQjN GdCWHGA s
(3BNQgG (B:s
(3hLGA TNU HhLY GdYVO SfI aTb YVOg aNQL efg eGOI YXejI aOGhGg HGdMGhQHhi hGdfNdi hGdPQhQ s
(3JGQjN fSN GdeNWhW gh SfI (B1810(3es
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B335 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B143s
(3HQhcdeGf edMb (B; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B212 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B(20434(3M(B) s
Keywords: (3GdJGQjNs